Analisis Shariah Compliance Pengajuan Komplain di Bukalapak - Muhammad Erfan; Ahmad Dakhoir; Mazrur Mazrur; ST. Rahmah (Al-Iqtishod : Jurnal Ekonomi Syariah, 2021)
Problems still arise in the online buying and selling process even though there are strict rules made by Bukalapak as a service provider. Violation of the rules by unscrupulous users will harm the buyer. To minimize violations, buyers are provided with facilities so that they can make complaints about the products received. Complaints and other processes that follow it seem like khiyar in Islamic law that needs to be analyzed based on shariah compliance. This research is a library research, with descriptive data presentation, data collection using documentation techniques and data analysis using Miles and Huberman models. The results of this study show an analysis of shariah compliance with the complaint process, the choice of reasons for the complaint and the choice of complaint solutions provided by Bukalapak. The results of the analysis show compliance with sharia principles based on the fatwa of the Dewan Syariah Nasional Majelis Ulama Indonesia (DSN-MUI) and the Kompilasi Hukum Ekonomi Syariah (KHES).